Optimizing self-expandable metallic stent placement for malignant ileocecal obstruction: Role of pre-stenting contrast enema and device selection - Maruyama, Akihiro; Nakayabu, Hiroshi; Takeshima, Hirotaka; Kato, Hiroki; Tominaga, Shintaro; Kobayashi, Makoto (Endoscopy International Open, 2025)
Self-expandable metallic stent (SEMS) placement is an established intervention for malignant colorectal obstruction, but the ileocecal region presents unique anatomical challenges. This study aimed to evaluate the technical success of SEMS placement for malignant ileocecal obstruction and to examine the impact of pre-stenting preparation and device selection.We retrospectively analyzed 72 patients with right-sided malignant colonic obstruction (13 ileocecal, 59 other segments) treated between January 2011 and March 2025. The primary outcome was the technical success rate; procedure efficiency was the secondary outcome. Clinical success was also evaluated in the ileocecal group according to treatment intent. All ileocecal cases underwent contrast liquid enema-assisted navigation (CLEAN) to assist device selection. Subgroup analyses examined scope diameter, hood shape, operator experience, and catheter tip mobility.Technical success was significantly lower in the ileocecal group (76.9% vs. 98.3%, P = 0.017), whereas median procedure times were similar (40.0 vs. 35.0 minutes, P = 0.934). In the ileocecal group, all patients with technical success also achieved clinical success. No major complications occurred. Tapered hoods significantly shortened procedure time (26.0 vs. 50.0 minutes, P = 0.018), and expert operators completed procedures faster than trainees (30.5 vs. 58.0 minutes, P = 0.042). Although movable-tip catheters and smaller-diameter scopes showed no statistical differences, selected cases demonstrated procedure advantages.SEMS placement in the ileocecal region is technically more challenging than in other right-sided segments. Procedure optimization – potentially aided by CLEAN, tapered hoods, and experienced operators—may help overcome anatomical difficulties while maintaining safety.
Keywords: Endoscopy Lower GI Tract; Stenting; Colorectal cancer; Quality and logistical aspects; Preparation